Technology and Learning : Issues Vital to Address - Sage,Rosemary (Educational Research E-Books Online, Collection 2023., 2024)
This book unpicks how the growing role of technology in learning, particularly tools and machines designed to solve real-world problems, is impacting thinking and expression. Discussed are processes, which must be understood to apply technology tools successfully; practices, to determine how to implement effective technology support to assist thinking, communication, and collaboration; performance, in terms of student experiences of technology; and predictions, to outline and analyze current technology trends. Contributors are: Nigel Adams, Peter Chatterton, Stefano Cobello, Bozydar Kaczmarek, Elizabeth Negus, Juan Romero and Tamas Rotschild